PENGUIN TINGKAT BAGI HASIL DAN UKURAN BANK TERHADAP JUMLAH SIMPANAN DEPOSITOMUDHARABAH PADA BANK UMUMSYARIAH DI INDONESIA - heni suryaningsih; marlina widiyanti; Taufik Taufik (JEMBATAN, 2017)
This study aimed to determine the effect of Profit Sharing Rate and The Size of the Bank together and partially to the Mudharabah Total Deposits in Islamic Bank in Indonesia period of 2013-2015. The Object of this study is Islamic Banks in Indonesia. The variables used in this study is Profit Sharing Rate and The Size of the Bank together and Mudharabah Total Deposits. Data analysis method used is Multiple Linear Regression. The results showed that the variable level of revenue sharing and the size of the bank jointly significant effect on the amount of savings deposits mudharabah. While predominantly known to the variable size of the bank which significantly affect the amount of savings deposits mudharabah. Implications of the study is that if the bank size increases, the greater the amount of savings bank deposits mudharabah obtained, so that the size of the banks may be determinant variables an investor in making an investment decision. Keywords : Profit Sharing Rate, The Size of Bank, and Mudharabah Deposits.